The Exhibition at the Nature Center in the Development of Creativity of the Bols is Also the Effectiveness of Practical Methods (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The method (from Greek “metohodos” –path) represents the path that elicits to the goal. The educational method is a way of interaction,aimed at solving the tasks of education, upbringing, development of an individual in the educational process,describes V.A.Slastyanin. in order to increase the effectiveness of the educational process, we use educational methods. Educational methods-a set of methods that are used in the educational process and ensure its effectiveness. There is no single definition of educational methods. The task of the methods is the regulation of the USLS of interoperability activities aimed at solving the educational and educational tasks of educators and educators. Y.I.Perovsky, N.M. Verzulin, Y.Ya. Golant classified the techniques into oral, visionary practical types. Methods are usually easier to learn further if we divide them into 2 types.